Age structure, condition and length increase of the topmouth gudgeon (Pseudorasbora parva Schlegel 1842) in non-native populations of small rivers of Poland - Czerniejewski Przemysław (Journal of Water and Land Development, 2019)
Monitoring studies of ichthyofauna, in particular non-indigenous species, are an important element of research on aquatic ecosystems. This information is essential for modelling population growth and predicting rates of expansion, quantifying ecological impacts and assessing the efficacy of removal and control strategies. Actually, the most compelling fish invasion in Polish freshwaters is arguably the accidental introduction of the topmouth gudgeon (Pseudorasbora parva). Age and lengths structure, condition factor and growth rate of the invasive populations of the topmouth gudgeon from small Polish rivers was examined. The samples were collected from the rivers: Molnica (n = 41), Myśla (n = 21) and Wardynka (n = 101) soon after the invasion was recorded (2017). Estimated ages of topmouth gudgeon ranged from 1+ to 3+ for the Myśla River, from 1+ do 4+ for the Molnica River, and from 1+ to 5+ for the Wardynka River. The fish from the Molnica River was characterised by the lowest total and standard length (TL, SL), weight, and highest condition. The results of back-calculations and the parameters of von Bertalanffy’s growth equation revealed distinct disproportions in the standard length (mm) in individual age groups (Molnica River: Lt = 54.94 [1 – e−0.68885 (1 − 0.003404)], Myśla River: Lt = 55.39 [1 – e−0.74921 (1 – 0.030962)], Wardynka River: Lt = 66.33 [1 – e−0.69348 (1 – 0.369505)]). The introduction of the topmouth gudgeon occurred in the upper and medium sectors of small rivers, but in subsequent years the species migrated to new sites further downstream and this may have affected the native ichthyofauna.